Immunosuppression and immunization: Vaccination in pediatric patients with neuromuscular diseases treated with steroids or immune-modulating drugs. (November 2021) - Golli, Tanja; Kastrin, Andrej; Pokorn, Marko; Rener-Primec, Zvonka
Abstract: Background: Modulating the immune response has proven to be beneficial in different neurologic diseases, even in those not perceived thus far to be autoimmune. Methods: Extensive literature search has been done for available data on vaccine safety, efficacy and immunization recommendations in patients with neuromuscular disease in general and when receiving immune-modulating treatments. Results: Vaccinations have been associated with some neuromuscular diseases, but these occurrences are very rare and should not influence the general vaccination recommendations for the pediatric population and for the especially vulnerable patient populations, such as neuromuscular disease patients. Specific guidelines for the immunization of children with neuromuscular diseases in general and those on immune-suppressive treatments were not found, but most guidelines and standards of care for specific neuromuscular diseases recognize and stress the importance of vaccinations, some giving more specific instructions. Conclusion: With just a few exceptions, vaccines are safe in this group of patients and they should receive the same immunizations and according to the same schedule, as all children. Live vaccines should not be administered in patients receiving high dose steroid or immune-modulating drugs such as anti-B cell treatments (rituximab), high dose methotrexate, azathioprine or 6-mercaptopurine. Whenever possible, all live vaccines should be administered prior to long term immune-suppressant treatments. Additional vaccines are recommended in this risk population of children (influenza, pneumococcal, varicella). Highlights: In general vaccines are safe in patients with neuromuscular disease. Children should receive the same immunizations as all children. Live vaccines should be administered prior to long term immune-suppressant treatments. Live vaccines are contraindicated during high doses of systemic corticosteroids or other immune-suppressive therapy. Additional vaccines are recommended in children with neuromuscular diseases.